Investigations of high temperature synergetic tribological behavior of HVOF deposited Ni-based metallic coating with self-lubricating ceramic phase (h-BN) - Gautam R.K.S.; Tripathi V.M.; Gautam J.K.; Jha P.; Sahab S.; Tyagi R.; Nautiyal H. (My University, 2025)
In the present investigation the influence of solid lubricants (Ag, MoS2, and h-BN) addition on the friction and wear properties of Ni-based coatings were studied. The coatings were deposited using high velocity oxygen fuel (HVOF) route with fixed concentration (10 wt%) of MoS2 and Ag while varying the weight percentages (0, 5, 7.5, and 10 wt%) of h-BN. However, the hardness of the coated samples was observed to decrease from 403 HV0.3 to 380 HV0.3 for 5 wt% h-BN, whereas it declined to 365 HV0.3 and 310 HV0.3 corresponding to the samples with 7.5 and 10 wt% of h-BN. Further, the tribological properties of coated specimens against Al2O3 ball were explored from room temperature (RT) to 800 °C. Commercial Al2O3 ceramic ball with diameter 6 mm was used as the counterpart. The friction coefficient and wear rate were observed to decrease with rise in temperature, particularly the coefficient of friction (COF) for the coated sample (7.5 wt% h-BN) dropped from 0.5 to 0.15. Moreover, the coating with 7.5 wt% h-BN showed the best tribological behavior tested under the aforesaid conditions. The favorable tribological properties of the coatings were explained and linked to the observed behavior on the basis of the combined effect of NiO, AgMoxOy, Ag, MoS2 and optimal concentration of h-BN. © 2023 Elsevier B.V.